Pengaruh Free Cash Flow dan Total Asset Turnover terhadap Price to Book Value pada Perusahaan Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2022-2025 - Naufal Syafiq Aprizal; Suryanto Sosrowidigdo; Siti Nurjanah (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
Firm value reflects the market's perception of a company's performance and future prospects, making it an important consideration for investors in making investment decisions. Price to Book Value (PBV) is one of the financial ratios commonly used to represent firm value. This study aims to examine the effect of Free Cash Flow (FCF) and Total Asset Turnover (TATO) on Price to Book Value (PBV) in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the 2022–2025 period. This study employed a quantitative approach using secondary data obtained from the companies' annual financial statements. The samples were selected through a purposive sampling technique, resulting in seven companies with a total of 28 observations. Data were analyzed using multiple linear regression with IBM SPSS Statistics. Since the data did not initially satisfy the normality assumption, the PBV variable was transformed using the natural logarithm (Ln) prior to the regression analysis. The findings reveal that Free Cash Flow and Total Asset Turnover have a positive and significant partial effect on Ln_PBV. Furthermore, both variables simultaneously have a significant effect on Ln_PBV. The Adjusted R Square value of 0.321 indicates that the research model explains 32.1% of the variation in Ln_PBV, while the remaining 67.9% is influenced by other factors outside the model. These findings emphasize that effective free cash flow management and optimal asset utilization contribute to improving the market valuation of a company.